Low frequency noise measurement in the MOS transistor - Thet, Kyaw Win. (2011)
Low frequency, 1/f noise measurements on a number of silicon dioxide gate dielectric based commercial MOS transistors and new material high-k gate dielectric transistors have been performed. The low frequency noise spectrum and the dependence of noise on the different gate dielectrics, channel lengths and bias gate and drain voltages have been examined for frequencies between 1 Hz and 100 kHz. It is found that 1/f noise increases with high-k dielectric in comparison with silicon dioxide gate dielectric, shorter channel lengths and higher bias gate voltage while drain voltage is kept small and constant at |0.1V|. The width of all the devices tested is 10um while different channel lengths of the range 0.12 – 0.5 um are measured experimentally.